2020
DOI: 10.5045/br.2020.s011
|View full text |Cite
|
Sign up to set email alerts
|

Extranodal NK/T cell lymphoma

Abstract: Extranodal natural killer (NK)/T cell lymphoma (ENKTL) is a distinct subtype of Non-Hodgkin's lymphoma mainly involving the nasal area. Since the entity was first recognized, treatment strategies have been evolving from anthracycline-based chemotherapy and radiotherapy to L-asparaginase containing regimens and recently immune checkpoint inhibitors. With the currently used combined chemotherapy and radiotherapy, more than 70% of patients with localized disease can be cured. L-asparaginase containing regimens ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 92 publications
(109 reference statements)
0
28
0
1
Order By: Relevance
“…The ENKL‐nasal type form is about 1%–2% of all NHL 1,77 . The ENKTL cells express CD2, CD3, CD45, CD56, and ICAM‐1 78 These mostly present as extranodal lymphomas characterized by vascular damage and destruction, necrosis, cytotoxic phenotype and presence of the EBV genome in the tumor cells. Note, ENKL are chemoresistant in part due to the high expression of P‐glycoprotein genes leading to drug resistance 79 .…”
Section: Molecular Pathogenesis Of Ptcl Subtypesmentioning
confidence: 99%
See 1 more Smart Citation
“…The ENKL‐nasal type form is about 1%–2% of all NHL 1,77 . The ENKTL cells express CD2, CD3, CD45, CD56, and ICAM‐1 78 These mostly present as extranodal lymphomas characterized by vascular damage and destruction, necrosis, cytotoxic phenotype and presence of the EBV genome in the tumor cells. Note, ENKL are chemoresistant in part due to the high expression of P‐glycoprotein genes leading to drug resistance 79 .…”
Section: Molecular Pathogenesis Of Ptcl Subtypesmentioning
confidence: 99%
“…Other important pathways include activation of the NOTCH pathway, upregulation of aurora kinase A which regulates mitosis, and upregulates the TP53 pathway to increase expression of survivin (BIRC5), and activation of the hypoxia induced pathway alpha which may promote tumorigenesis and angiogenesis 10 . These tumors tend to be radiosensitive and incorporation of radiotherapy has resulted in improved outcomes at least in limited disease 78 . The treatment paradigm for ENKL is shown in Figure 3.…”
Section: Molecular Pathogenesis Of Ptcl Subtypesmentioning
confidence: 99%
“…Primary colonic ENKTL-NT is very rare and difficult to identify in the early stages due to the lack of characteristic clinical symptoms and other evidence. Although histologically ENKTL-NT presents as an ulcerative granuloma, differential diagnosis by endoscopic examination is difficult because of other benign Case Report granulomatous proliferative diseases of the colon and malignant neoplasms, which can easily lead to misdiagnosis, and the final diagnosis depends on immunohistochemical analysis of tissue specimens (5). Here, we present a rare case of primary colonic ENKTL-NT, in accordance with the CARE reporting checklist (available at https://dx.doi.…”
Section: Introductionmentioning
confidence: 85%
“…ENKTL-NT begins with abnormal transformation and proliferation of EBV-infected NK cells or T-cells (4). More than 70% of ENKTL-NT cases occur in the nose and the tumor is confined to the adjacent area, but can occur at other sites (5). In an epidemiological study, it was noted that the distribution of ENKTL-NT subtypes did not correlate with country geography or ethnicity (6).…”
Section: Introductionmentioning
confidence: 99%
“…L-Asparaginase or pegylated asparaginase containing regimens are widely used in the treatment of advanced and relapsed/refractory ENKTL [ 26 , 27 ]. Since the outcomes of various treatment regimens currently used are still poor, several novel approaches targeting for PD-1/PD-L1 [ 28 ], LMP1/LMP2 [ 29 ], and JAK/STAT pathway (NCT02974647) are being conducted in ENKTL [ 30 ], and STAT5 [ 31 , 32 ] in MEITL. In ALCL, CHOP or CHOP plus etoposide remains the first-line therapy [ 33 ] and recent clinical trials with anti-CD30 antibody (brentuximab vedotin) have shown substantial activity in the relapsed or refractory disease [ 34 ] and front-line treatment [ 35 ].…”
Section: Discussionmentioning
confidence: 99%